Repurposing the selective estrogen receptor modulator bazedoxifene to suppress gastrointestinal cancer growth - Pathum Thilakasiri; Jennifer Huynh; Ashleigh R Poh; Chin Wee Tan; Tracy L Nero; Kelly Tran; Adam C Parslow; Shoukat Afshar‐Sterle; David Baloyan; Natalie J Hannan; Michael Buchert; Andrew Mark Scott; et al. (EMBO Molecular Medicine)
Abstract Excessive signaling through gp130, the shared receptor for the interleukin (IL)6 family of cytokines, is a common hallmark in solid malignancies and promotes their progression. Here, we established the in vivo utility of bazedoxifene, a steroid analog clinically approved for the treatment of osteoporosis, to suppress gp130‐dependent tumor growth of the gastrointestinal epithelium. Bazedoxifene administration reduced gastric tumor burden in gp130Y757F mice, where tumors arise exclusively through excessive gp130/STAT3 signaling in response to the IL6 family cytokine IL11. Likewise, in mouse models of sporadic colon and intestinal cancers, which arise from oncogenic mutations in the tumor suppressor gene Apc and the associated β‐catenin/canonical WNT pathway, bazedoxifene treatment reduces tumor burden. Consistent with the proposed orthogonal tumor‐promoting activity of IL11‐dependent gp130/STAT3 signaling, tumors of bazedoxifene‐treated Apc‐mutant mice retain excessive nuclear accumulation of β‐catenin and aberrant WNT pathway activation. Likewise, bazedoxifene treatment of human colon cancer cells harboring mutant APC did not reduce aberrant canonical WNT signaling, but suppressed IL11‐dependent STAT3 signaling. Our findings provide compelling proof of concept to support the repurposing of bazedoxifene for the treatment of gastrointestinal cancers in which IL11 plays a tumor‐promoting role.